Studies on Tissue Specific Variation and Developmental Variation in the Isoperoxidase Pattern of the Selected Endemic Tree Species of Western Ghats - M*, Johnson (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The present study was aimed to study the isoperoxidase pattern<span style="line-height: 110%; font-family: ";Times New Roman";,";serif";; color: blue; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">of the seeds and adult plant leaves of the endemic tree species viz., Hopea utilis <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10.5pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: Calibri; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Bedd.Â Bole<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">,<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> Poeciloneuron pauciflorum Bedd, Gluta travancorica Linn and Garcinia travancorica Bedd of Western Ghats, India. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">A total of 41 bands in 23 different locations with five active regions were observed in the isoperoxidase system of the selected endemic tree species. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The seeds of Hopea utilis showed totally eight bands with different MW-Rf values viz., 0.06, 0.097, 0.131, 0.205, 0.254, 0.296, 0.356 and 0.422. Of which, the bands with MW-Rf values 0.06 and 0.356 was shared by the seeds and adult plant leaves of Hopea utilis. The seeds of P. pauciflorum collected from kannikatty showed four bands (0.051, 0.276, 0.322 and 0.402) with four active zones.Â The band with MW-Rf value 0.402 was shared by the seeds of P. pauciflorum collected from kannikatty and Inchikuzhi. The seeds of P. pauciflorum collected from Inchikuzhi showed only two bands with MW-Rf values 0.319 and 0.402. A total of 7 bands in six different positions with four activity regions were observed in the isoperoxidase enzyme system of Gluta travancorica. A total of six bands from different positions were observed in seeds of Garcinia travancorica and six in adult plant leaves of G. travancorica were observed in this enzyme system and their Rf values ranged from 0.097 to 0.484. Multiple zone of activity was observed for this enzyme system (PRX 1 to 5). The results of peroxidase activity and pattern changes in the seeds and adult plant leaves of the selected endemic tree species viz., suggest that each isoperoxidase or groups of isoperoxidase function in different capacities and over-all banding pattern of isoperoxidase may help in the identification of the endemic tree species.